2014
DOI: 10.1016/j.psychres.2014.06.023
|View full text |Cite
|
Sign up to set email alerts
|

The content of attenuated psychotic symptoms in those at clinical high risk for psychosis

Abstract: Recent research has started to focus on identifying individuals who are at clinical high risk of developing psychosis as a means to try and understand the predictors and mechanisms involved in the progress to a full psychotic episode. The aim of the current study was to provide an initial description and prevalence rates of specific content found within attenuated positive symptoms. The Content of Attenuated Positive Symptoms (CAPS) codebook was used by independent raters to determine the presence of content w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…CAPS codebook items are assigned a numeric code with items dichotomously coded as 0 (absent in the vignette) or 1 (present in the vignette). Using this coding scheme, a prior interrater reliability analysis (Marshall et al, 2014) reported higher than ‘acceptable’ (>70%) (Krippendorff, 2012) reliabilities for the majority (83.33%) of the CAPS items.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…CAPS codebook items are assigned a numeric code with items dichotomously coded as 0 (absent in the vignette) or 1 (present in the vignette). Using this coding scheme, a prior interrater reliability analysis (Marshall et al, 2014) reported higher than ‘acceptable’ (>70%) (Krippendorff, 2012) reliabilities for the majority (83.33%) of the CAPS items.…”
Section: Methodsmentioning
confidence: 96%
“…Symptom coding of case vignettes was completed by two raters, each of whom was trained on the CAPS codebook (Marshall et al, 2014). The content items of perceptual abnormalities were then used to generate the subtypes.…”
Section: Methodsmentioning
confidence: 99%
“…The SIPS was designed to detect attenuated positive symptoms (i.e., psychotic symptoms below the threshold of full-blown psychotic symptoms; Marshall et al, 2014; Miller et al, 2003). Its developers did not say it was designed to for use only in treatment seeking samples, but it has mostly been used in clinical populations at ultra-high risk for psychosis onset.…”
Section: Methodsmentioning
confidence: 99%
“…This hypothesis is supported by evidence that more severe unusual ideas and beliefs at baseline predict the steeper rate of gray matter loss in superior and medial PFC bilaterally among CHR cases progressing to full psychosis [47] (Fig 2b). As such, disruptions in source memory may underlie the earliest appearing prodromal symptoms, which include perplexity or confusion about what is real versus imaginary, changes in the perception of time, and changes in the interpretation of events and experiences such that the familiar begins to feel strange, confusing, ominous, threatening, or otherwise to have special meaning [48]. Over time, more elaborate beliefs – such as alien control of thought, ideas of reference, and systemized persecutory delusions – may be built up as explanations of the faulty source attributions and generalized sense of foreboding, and skepticism in these explanations may erode as an increasing proportion of experience salient in memory is subject to source confusion.…”
Section: Neurodevelopment Medial Prefrontal Cortex and Errors In Somentioning
confidence: 99%